Distribution of chromium and gallium in the total suspended solid and surface sediments of Sungai Kelantan, Kelantan, Malaysia - Mohamad Arif Che Abd Rahim,; Aniruth A/L Aproi,; Shi, Xuefa; Liu, Shengfa; Masni Mohd Ali,; Wan Zuhairi Wan Yaacob,; Che Abd Rahim Mohamed, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Concentration level of chromium (Cr) and gallium (Ga) were measured in the total suspended solid (TSS) and surface sediments to investigate its distribution and anthropogenic inputs along Sungai Kelantan. The in-situ water quality parameters, surface sediment and surface water were collected using calibrated portable YSI water quality meter, ponar grab and water sampler, respectively. The concentration range of chromium and gallium in TSS were from 19-111 μg/g and 153-3762 μg/g, respectively, along the river. While in surface sediment, the concentrations ranged from 16-172 μg/g for Cr and 25-82 μg/g for Ga. The high concentration of Ga in TSS and Cr in sediment would suggest that the anthropogenic inputs takes place in the river channel, which is due to human activities such as sand exploration along Sungai Kelantan. In mobilization towards the estuary, Ga was more easily transported in the TSS from upstream to downstream especially during the wet season. Cr was dominant in sediment due to its affinity towards inorganic minerals and easily being scavenged in the water column during burial onto the riverbed sediment. Spatial distribution was prominent as several factors affecting the distribution along the river channel addresses the lighter gallium and dissolution of chromium towards surface sediment while being mobilize further for overall distribution before sinking in the estuarine region.